Hip Abduction Pillow untuk Menurunkan Resiko Dislokasi pada Pasien Pasca Operasi Total Hip Replacement - Luluk Nafisah; Masfuri Masfuri; Liya Arista (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Malposition of the acetabular component is a risk factor for postoperative dislocation. This study aims to identify and review studies related to the effectiveness of the use of a hip abduction pillow in reducing the incidence of dislocation in postoperative total hip replacement patients. The sources used are several online databases, namely Scopus, ScienceDirect, and SpringerLink published from 2000-2021. With keywords “Hip Abduction Pillow”, “Leg Abductor Cushion”, “adductor pillow”, “Concave Hip Abduction”, “Post Total Hip Replacement surgery”, “dislocation post total Hip replacement”, “Hip replacement”, and total hip replacement intervention". It was found that dislocation affects the occurrence of revision surgery. Risk factors that lead to THR revision surgery are younger age, greater comorbidities, diagnosis of avascular necrosis (AVN), larger femoral head size, male gender -male, longer operating time, and smaller size of the femoral head.Hip abduction pillow intervention has been shown to have little effect on the occurrence of dislocations in patients after total hip replacement surgery.Keywords: dislocation; hip abduction pillow; post surgery total hip replacement ABSTRAK Malposisi dari komponen acetabular merupakan salah satu resiko penyebab terjadinya dislokasi pasca operasi. Penelitian ini bertujuan untuk mengetahui serta meninjau dari penelitian-penelitian yang berkaitan dengan efektifitas penggunaan hip abduction pillow dalam menurunkan kejadian dislokasi pada pasien pasca operasi total hip replacement. Sumber yang digunakan adalah beberapa online database yakni Scopus, ScienceDirect, dan SpringerLink terbitan dari tahun 2000-2021. Dengan kata kunci "Hip Abduction Pillow", “Leg Abductor Cushion”, “adductor pillow”, “Concave Hip Abduction”, “Post Total Hip Replacement surgery”, "dislocation post total Hip replacement", "Hip replacement ", dan total hip replacement intervention". Didapatkan hasil bahwa dislokasi mempengaruhi terjadinya operasi revisi ulang. Faktor risiko yang mengakibatkan tindakan revisi operasi THR adalah usia yang lebih muda, komorbiditas yang lebih besar, diagnosis nekrosis avaskular (AVN), ukuran kepala femoralis yang lebih besar, jenis kelamin laki-laki, waktu operasi yang lebih lama, dan ukuran kepala femoralis yang lebih kecil. Intervensi Hip abduction pillow terbukti tidak banyak mempengaruhi terjadinya dislokasi pada pasien pasca operasi total hip replacement. Kata kunci: dislokasi; hip abduction pillow; pasca operasi total hip replacement